Figuras geométricas planas e ângulos com Geogebra: uma integração da tecnologia no ensino médio da EJA - Galvão, Celina Rodriguês (Brasil, 2023)
This monographic work of course completion aims to understand the importance of integrating the use of digital tools in the student's daily life to recognize, classify and compare angles in plane geometric figures, and in particular with the use of GeoGebra software. The research was conducted in the State School Maria Ivone de Araújo Leite, located in Nossa Senhora do Rosário Street, São Jorge neighborhood, Itacoatiara-AM City, with a class of high school students of the 11th stage (3rd year) of EJA (Education for Youth and Adults) of the night shift. The methodology used was the qualitative approach and as instruments of data collection the questionnaire, the interview and direct observation. The main resource of the research to identify angles in plane geometric figures was the GeoGebra software installed in the computers of the computer lab. The work was developed in the computer lab in three moments. In the first moment the subject was explained through the contextualization of the students' lives and experiences, in order to promote the construction of their knowledge. In the second moment some plane geometric figures were presented so that the students could verify the angles using a protractor and then the skills and knowledge were put into practice using the GeoGebra software, thus finding angles, areas and perimeter in the plane geometric figures. In the third moment a multiple choice test was performed regarding the development of the content about plane geometric figures and angles in the Kahoot learning platform. It is believed that working with plane geometric figures and angles in GeoGebra software can contribute to the teaching learning process of students, not only based on concepts, but also in dynamic practices.